Tele-Dentistry And Public Health Dentistry: A Literature Review (Indian Journal of Public Health Research & Development, 2023)
Tele-dentistry has a history going back to 1994. The main concept of tele-dentistry proposes the application ofinformation and communication technologies (ICT) to facilitate oral healthcare for geographically distant patientsand/or practitioners. It also allows dental professionals to communicate with one another over long distances.It not only has the potential to increase accessibility of specialists, but also decreases time and cost associatedwith speciality consultations. The aim of this article is to present an overview of the uses of information andcommunication technologies in oral health.
Keywords: Public health dentistry, real-time video conferencing, telecommunications, tele-dentistry, telemedicine.